Traditional earthquake resistant techniques for vernacular architecture and local seismic cultures: A literature review - Ortega, Javier (2022)
Specific architectural elements can be identified in constructions located in regions frequently exposed to earthquakes. These earthquake resistant features were developed empirically by local communities to protect their built-up environment. Research in these traditional earthquake resistant practices, resulting from a local seismic culture, is a relevant and positive approach, since it focuses on the strengths of a system rather than on its weaknesses. Its integration into current vernacular building practices can help to preserve and retrofit surviving in-use examples without prejudice to their identity. This paper presents an overview of the most common techniques traditionally used around the world, based on literature review. Additionally, it identifies the use of these techniques in the Portuguese vernacular heritage in order to contribute for the awareness and strength of the local seismic culture in Portugal.